Renewables, Shale Gas and Gas Import- Striking a Balance for India. (May 2017) - Negi, B.S.; Pandey, K.K.; Sehgal, Neha
Abstract: India's primary energy basket is heavily weight in favour of coal, oil and gas (92%) and balance 8% renewables, hydro and nuclear. The eco-friendly energy resources like natural gas and renewables (wind & solar) account only for 9% and 2%. The long term energy demand forecast also suggests contribution of coal, oil and gas to slide down to 87%. The Natural gas demand though on increase but the consumption is constrained due to limited domestic production and inadequacy of LNG import facilities. Considering the huge import bill on oil, gas and coal imports (150 billion, Kelkar 2013) and the ever increasing concern for environment, the eco-friendly non-conventional resources as shale gas are getting preference. This paper examines the potential contribution from Shale Gas to meet the energy demand to fuel the economic growth of India